DESIGNING AND IMPLEMENTING I-BIKE MOTORCYCLE RENTAL SYSTEM (CASE STUDY IN TIAN QI DIANDONG CHE XING, NANTONG, CHINA) - Wenni Puspa Sari; Suhendro Yusuf Irianto; Sken Jian Tao (Proceeding International Conference on Information Technology and Business, 2020)
I-bike motorcycle rental was the considerable and well-known business entity in China. The problem statement of this study was that this i-bike motorcycle rental system at Tian Qi Diandong Che Xing, in Nantong, Jiangsu Province was not effective. It was because the booking system was still done manually and most of local Chinese people was not able to speak English so that it caused difficulty for foreigners who wanted to rent this i-bike motorcycle. The objective of this study was designing the website-based system for the i-bike motorcycle. The application was designed through Adobe Dreamweaver CS5 and My SQL. This application was expected to provide detailed and accurate information about this i-bike motorcycle rented to the prospective tenants online from whom the companies were assisted to promote their motorbikes to foreigners with a website-based application system in English and to process the transactions, the data management, and the company reports.Keyword: I-bike motorcycle rental, China, Adobe Dreamweaver CS5, and My SQL